“Embedding” and “pulling back”: Spatial transformations and urban assimilation of migrant elderlies following their children - Bao, Yaxiong; Tao, Juanmei; Liu, Qian (Frontiers in Public Health, 2022)
Background Due to the rapid acceleration of social mobility and the shrinking size of families, China has begun to enter a new form of aging society, with an increasing number of migrant elderlies following their children. How to adapt and assimilate into the new living space profoundly affects those migrant elderlies' mental health. Drawing on the spatial framework proposed by Henry Lefebvre, this paper explores the factors affecting urban assimilation of migrant elderlies following their children in China, and puts forward corresponding strategies to promote the urban assimilation. Method Using semi-structured interviews and participatory observation, this study conducted a qualitative study among migrant elderlies following their children who lived in a University Community in Wuhan city, Hubei Province from May 2022 to July 2022. During the survey period, we participated in the gathering activities of the migrant elderly five times a week, and conducted semi-structured interviews with 15 migrant elderlies following their children. Results Firstly, this study reveals that family assimilation is the foundation of urban assimilation of migrant elderly following their children; Secondly, we could conclude that the urban life of the migrant elderlies are mostly community-based, so it is especially important for them to reconstruct close neighborhood relations and regain the humanity affection of the traditional acquaintance society. Lastly, the fundamental institutional barrier is a significant factor that influences the ability of these migrant elderlies to live a stable urban life. The Chinese government needs to promote a nationwide unified pension and health insurance system, so that the migrant elderlies can enjoy the same benefits as the local elderly residents in the “inflow” area.